Standardisation of Nursery Technique of Tropical Pines I. Hastening Germination of Pinus caribaea (var. Hondurensis) and Pinus patula Seeds - Ghosh, R. C.; Singh, R. P.; Sharma, K. K. (Indian Forester, 1974)
As prolongation of the time of germination exposes the valuable seeds of Pinus caribaea & P. patula to several risks, trials were undertaken to use a number of cheap and easily available agents for hastening germination. HCI, HCIO4, cowdung, boiling water and combinations of different durations of soaking and concentrations of H2O2, thiourea sol., KNO3 sol. and water were tried. Lower strengths of H2O2 when used for shorter durations proved effective in both of the cases, albeit for P. patula soaking in water for 18 hrs at ambient temperature was best in increasing overall germination. Higher strengths of H2O2 and higher soaking periods proved inhibitive in case of P. patula; 0.25% to 0.5% thiourea sol. and 0.5% to 1% KNO3 sol. inhibited germination of P. caribaea seed whereas cowdung and boiling water brought down the germination % of the both. Hydrochloric acids proved ineffective except in case of P. caribaea, but there too, it was inferior to H2O2 (3 to 6%) when used for 6 to 18 hrs.